2017
DOI: 10.1016/j.bpj.2016.11.2284
|View full text |Cite
|
Sign up to set email alerts
|

Eg5 Inhibitors have Contrasting Effects on Microtubule Stability and Spindle Integrity Depending on their Modes of Action

Abstract: Despite its fundamental importance to understanding the molecular bases of these cellular processes, a quantitative and testable mechanochemical model that describes how structural differences between kinesins alter kinetic steps in the ATPase cycle to produce functional changes in processivity is lacking. Here we use high resolution single-molecule microscopy to directly observe the stepping behavior of kinesin-1 and À2 motors with different neck linker lengths. We identify a one-head bound vulnerable state w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, our last epistatic analysis showed that eg5 acts upstream of gli2. Since Eg5 is considered an essential kinesin during microtubule organization and stability (Chen et al, 2017) with a participation in NC development different from its classical function in cell division (Fernandez et al, 2014), it is conceivable that Eg5 could act in the process required for Gli2 translocation to the primary cilium of Xenopus NCC. Moreover, this kinesin is highly expressed in glioblastoma cells as it is the case of Gli2 (Taglieri et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, our last epistatic analysis showed that eg5 acts upstream of gli2. Since Eg5 is considered an essential kinesin during microtubule organization and stability (Chen et al, 2017) with a participation in NC development different from its classical function in cell division (Fernandez et al, 2014), it is conceivable that Eg5 could act in the process required for Gli2 translocation to the primary cilium of Xenopus NCC. Moreover, this kinesin is highly expressed in glioblastoma cells as it is the case of Gli2 (Taglieri et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%